MOTILITY OF FROZEN THAWED SEMEN AFTER THERMAL RESISTANCE TEST - MATHUR, A K; KUMAR, S; PRABHAKAR, J H; MANDAL, D K; INGALE, H R; JAMES, JOSE (The Indian Journal of Animal Reproduction, 2023)
The data used in this study is an outcome of visit of Central Monitoring Unit (CMU) for evaluation ofSemen Station of Kerala and Chitely Dairy, Maharashtra. To assess the post-thaw motility of frozen semen,frozen straws were taken out randomly from the stored semen and were thawed at 37° C for 15 secondsand motility was recorded. The same samples were subjected to thermal incubation test in water bath at37° C and progressive motility (%) was recorded at 30 and 60 minutesafter incubation. It was observed thatthe mean post-thaw motility in exotic breeds (HF and Jersey) was 52.40 per cent followed by 50.85 percent in crossbreds (HF,Jersey, and other crosses).The per cent mean value observed in Indigenous breeds(Tharparkar and Gir) was 45.0 per cent and the difference in post thaw motility was non significant (p
Keywords: Percent motility; Frozen thawed semen; Crossbred bull; Incubation test